Method for measuring concentration of free iron ions in lithium ion battery electrolyte

By forming a stable complex with tannin acid and measuring with a Unisex spectrophotometer, the problem of high cost of measuring free iron ions in the lithium-ion battery electrolyte in the prior art is solved, and the measurement method is low-cost, easy to operate and good reproducibility is realized, and the battery quality is effectively controlled.

CN119827440APending Publication Date: 2025-04-15HUNAN XIANGDIAN POWER TEST & RES TECH LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807905.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing method of measuring free iron ions in lithium-ion battery electrolytes is costly, complex in operation, and poor in reproducibility, making it difficult to effectively control the battery quality.

Method used

By mixing tannin acid with free iron ions in the lithium-ion battery electrolyte, a stable complex was formed, and the absorbance was measured using an ultraviolet-visible spectrophotometer, and a standard curve was established to quantitatively determine the concentration of free iron ions.

Benefits of technology

The measurement of free iron ions in the lithium-ion battery electrolyte is achieved at low cost, easy to operate and reproducible, and the quality of the battery can be effectively controlled and the short circuit in the battery caused by the formation of iron-branched crystals is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827440A_ABST
    Figure CN119827440A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a method for measuring the concentration of free iron ions in lithium ion battery electrolyte. According to the invention, tannic acid is used as a detection reagent, the tannic acid and free iron ions form a stable complex, and the tannic acid has maximum absorption at 512nm under an ultraviolet-visible absorption spectrum. According to the method, the concentration of the free iron ions in the lithium ion battery electrolyte can be measured by utilizing the ultraviolet and visible spectrophotometer, the method is simple, efficient, low in cost and good in reproducibility, the relative error between the concentration of the free iron ions and the concentration of the free iron ions obtained by inductively coupled plasma-mass spectrometry does not exceed 6%, and the method is suitable for production of a lithium ion battery production line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium ion batteries, and in particular to a method for measuring the concentration of free iron ions in an electrolyte of a lithium ion battery. Background Art

[0002] Among lithium-ion batteries, the free iron ions contained in lithium iron phosphate batteries play a vital role in the safe and stable operation of the battery. During the use of the battery, the iron ions in the electrolyte, negative electrode and positive electrode will continue to dissolve in the electrolyte, and further electro-reduced and deposited on the negative electrode. The deposited iron ions are prone to form branched crystals, causing short circuits in the battery. Not only lithium iron phosphate batteries, but other types of lithium-ion batteries, such as batteries with lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide or ternary materials as positive electrode materials, may also introduce iron impurities during the preparation process, leading to the above problems. Therefore, the measurement of free iron ions in the electrolyte of lithium-ion batteries is of great significance in the control of battery quality.

[0003] At present, the main method for determining the iron content of different materials in lithium-ion batteries is through inductively coupled plasma-mass spectrometry. However, the instruments required for this method are expensive. At the same time, since the accuracy of the determination of free iron content in lithium-ion batteries is not high and it is only used as a quality control item, the cost-effectiveness of using this method is not high.

[0004] Therefore, how to provide a low-cost, easy-to-operate, and reproducible method for determining the content of free iron in lithium-ion battery electrolyte has become a problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above technical problems, the present disclosure provides a method for determining the concentration of free iron ions in a lithium-ion battery electrolyte. The method is low-cost, easy to operate, and has good reproducibility, and has good application prospects.

[0006] In a first aspect, the present disclosure provides a method for determining the concentration of free iron ions in a lithium ion battery electrolyte, the method comprising:

[0007] To create a standard curve:

[0008] S1: Mix the iron source with the blank electrolyte to prepare at least three free iron ion standard solutions with different concentrations;

[0009] S2: mixing tannic acid with free iron ion standard solutions of different concentrations respectively, so that tannic acid and free iron ions form a complex, and at least three mixed solutions are obtained accordingly;

[0010] S3: using the blank electrolyte as a reference solution, measuring the absorbance of the at least three mixed solutions at 512 nm using a UV-visible spectrophotometer, and establishing a standard curve of absorbance-free iron ion concentration;

[0011] Sample determination:

[0012] (1) mixing the electrolyte to be measured with tannic acid, so that the tannic acid forms a complex with the free iron ions in the electrolyte to be measured, thereby obtaining a mixed solution to be measured;

[0013] (2) Using the blank electrolyte as a reference solution, the absorbance of the mixed solution to be measured at 512 nm is measured using an ultraviolet-visible spectrophotometer, and the obtained absorbance data is substituted into the standard curve to calculate the free iron ion concentration in the electrolyte to be measured.

[0014] The protonated phenolic group of tannic acid is not a good ligand for metal cations. However, once the hydrogen atoms of the phenolic group are neutralized, the phenolic hydroxyl group exists in the form of oxygen anions, which can react with metal ions to form stable complexes. In addition, although some of the phenolic hydroxyl groups in tannic acid do not participate in the coordination reaction, it can still promote the delocalization of the lone pair associated with the other two hydroxyl groups and stabilize the complex. In the present disclosure, when the lithium-ion battery is formed, the iron ion concentration in the electrolyte is fixed, and tannic acid can form a stable complex with it (the coordination number of iron ions and tannic acid is 1:3). At the same time, since tannic acid has a large number of benzene rings, it will cause the maximum absorption peak of iron ions to move (maximum absorption at 512nm), and the concentration of the complex is proportional to the concentration of free iron ions within a certain range (1 mol of complex corresponds to 1 mol of iron ions). Based on this, the present disclosure utilizes the above mechanism, establishes a standard curve of free iron ions in lithium-ion battery electrolyte, and uses an ultraviolet spectrophotometer to quantitatively measure the free iron ions in the lithium-ion battery to be tested, thereby controlling the quality of the lithium-ion battery and avoiding the formation of iron branch crystals that cause short circuits in the battery. Compared with the existing inductively coupled plasma-mass spectrometry measurement technology, it is low-cost, easy to operate, and has good reproducibility, and has good application prospects.

[0015] Generally, in order to ensure that all the iron ions in the electrolyte can completely form a complex with tannic acid, tannic acid needs to be added in excess.

[0016] It should be further explained that the blank electrolyte refers to the prepared electrolyte stock solution that has not been formed; and the electrolyte to be measured is the blank electrolyte that has been formed after being assembled into a lithium-ion battery.

[0017] The following are preferred technical solutions of the present disclosure, but are not intended to be limitations of the technical solutions provided by the present disclosure. Through the following technical solutions, the technical objectives and beneficial effects of the present disclosure can be better achieved and realized.

[0018] As a preferred technical solution of the present disclosure, the tannic acid is added in the form of a tannic acid solution;

[0019] The solvent in the tannic acid solution is a blank electrolyte, and the concentration of tannic acid is 0.001-0.01 mol / L, for example, 0.001 mol / L, 0.002 mol / L, 0.004 mol / L, 0.006 mol / L, 0.008 mol / L or 0.01 mol / L, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0020] In the present disclosure, considering that the concentration of free iron ions in lithium-ion batteries is at the ppm level, a 0.001 mol / L tannic acid solution can accurately measure the concentration of free iron ions. The concentration of tannic acid should not be too high, otherwise it will cause the electrolyte solute to precipitate, which will affect the measurement results.

[0021] As a preferred technical solution of the present disclosure, in step S2, the molar ratio of the tannic acid to the free iron ions in the standard solution is above 3, such as 3, 4 or 5, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable, preferably 4-4.5.

[0022] As a preferred technical solution of the present disclosure, in step S1, the iron source includes ferric chloride.

[0023] As a preferred technical solution of the present invention, in step S2, the concentration range of the iron element in the at least three mixed solutions is 0.0005-0.05mmol / L, for example, 0.0005mmol / L, 0.005mmol / L, 0.01mmol / L, 0.03mmol / L or 0.05mmol / L, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0024] As a preferred technical solution of the present invention, in step S1, the concentration range of the free iron ion standard solution of different concentrations is 0.001-0.1mmol / L, for example, 0.001mmol / L, 0.005mmol / L, 0.01mmol / L, 0.04mmol / L, 0.05mmol / L, 0.08mmol / L or 0.1mmol / L, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0025] Furthermore, the concentration range of the free iron ion standard solution corresponds to an absorbance of 0.06-1.32 as measured by an ultraviolet spectrophotometer.

[0026] The concentration of the complex formed by iron ions and tannic acid is proportional to the concentration of iron ions within the above concentration range (1 mol of the complex corresponds to 1 mol of iron ions). Within the above concentration range, the iron ion concentration can be quickly and accurately measured and calculated to control the battery quality.

[0027] The minimum detection limit of the iron ion concentration in the method disclosed in the present invention is 0.001 mmol / L; if the concentration of iron ions in the electrolyte to be measured is higher than 0.1 mmol / L, that is, the corresponding absorbance is greater than 1.32, then the concentration of free iron ions exceeds the detection range of the present method, and a blank electrolyte needs to be used to dilute it to within the detection range of the present method to obtain accurate results.

[0028] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0029] The present invention uses tannic acid as a detection reagent, which forms a stable complex with free iron ions and has a maximum absorption at 512nm under the ultraviolet visible absorption spectrum. The present invention uses an ultraviolet visible spectrophotometer to measure the concentration of free iron ions in lithium ion battery electrolytes. It is simple and efficient, low cost, and has good reproducibility. The relative deviation of the free iron ion concentration obtained by inductively coupled plasma-mass spectrometry does not exceed 6%, and is suitable for the production of lithium ion battery production lines. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0032] Figure 1 This is the standard curve fitting diagram in Example 1 of the present disclosure. DETAILED DESCRIPTION

[0033] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0035] Example 1

[0036] This embodiment provides a method for determining the concentration of free iron ions in a lithium ion battery electrolyte, the method comprising:

[0037] Prepare blank electrolyte:

[0038] The solvent composition is dimethyl carbonate:ethylene carbonate:propylene carbonate=1:1:1 (volume ratio);

[0039] The solute is 1 mol / L lithium hexafluorophosphate;

[0040] S1: Dissolve 1.7 g of tannic acid in 80 mL of the blank electrolyte, then transfer the solution to a 100 mL volumetric flask, and use the blank electrolyte to make up the volume to prepare a tannic acid solution with a concentration of 0.01 mol / L;

[0041] Dissolve 0.0162g of ferric chloride in 80mL of the blank electrolyte, then transfer the solution to a 100mL volumetric flask, use the blank electrolyte to make up to volume, and prepare a free iron ion solution with a concentration of 1mmol / L; then dilute the free iron ion solution with a concentration of 1mmol / L into: 0.1mmol / L free iron ion solution, 0.03mmol / L free iron ion solution, 0.01mmol / L free iron ion solution, 0.005mmol / L free iron ion solution and 0.001mmol / L free iron ion solution respectively through a volumetric flask;

[0042] S2: 2 mL of the tannic acid solution is mixed with 2.5 mL of free iron ion solutions of different concentrations respectively to form a complex between the tannic acid and the free iron ions, and then the mixture is transferred to a 5 mL volumetric flask and fixed to volume with the blank electrolyte to obtain at least 5 mixed solutions;

[0043] S3: Using the blank electrolyte as the reference solution, the absorbance of at least five mixed solutions at 512 nm is measured by UV-visible spectrophotometer, and a standard curve is obtained by fitting with the absorbance as the ordinate and the free iron ion concentration as the abscissa. The fitting result is as follows: Figure 1 As shown;

[0044] The linear equation of the obtained standard curve is A = 0.0403 + 12.71C, and the correlation coefficient is R 2 The value was 0.9993, indicating that the standard curve had a good linear relationship within the concentration range (R 2 >0.9900);

[0045] Where A represents the absorbance at 512 nm; C represents the free iron ion concentration in the electrolyte to be measured, mmo1 / L.

[0046] Sample determination:

[0047] The electrolyte to be measured is a lithium-ion battery, and the electrolyte obtained after injection of the blank electrolyte and formation is the electrolyte to be measured;

[0048] (1) 2.5 mL of the electrolyte to be measured was mixed with 2 mL of a 0.01 mol / L tannic acid solution to form a complex with the tannic acid and the free iron ions, and then the mixture was transferred to a 25 mL volumetric flask and fixed to volume with the blank electrolyte to obtain a mixed solution;

[0049] (2) Using the blank electrolyte as a reference solution, the absorbance of the mixed solution at 512 nm was measured using an ultraviolet-visible spectrophotometer, and the free iron ion concentration in the electrolyte to be measured was calculated based on the obtained absorbance and the linear equation of the standard curve.

[0050] According to the above process, 10 parallel tests were carried out, and the measurement results are shown in Table 1.

[0051] Table 1

[0052]

[0053] As can be seen from Table 1, the discreteness of the determination method disclosed in the present invention is low and the reproducibility is high, which can meet the control of the quality of lithium-ion batteries.

[0054] Example 2

[0055] This embodiment provides a method for determining the concentration of free iron ions in a lithium ion battery electrolyte, the method comprising:

[0056] Prepare blank electrolyte:

[0057] The solvent composition is dimethyl carbonate:ethylene carbonate:propylene carbonate=2:2:1 (volume ratio);

[0058] The solute is 1 mol / L lithium hexafluorophosphate;

[0059] S1: Dissolve 1.7 g of tannic acid in 80 mL of blank electrolyte, then transfer the solution to a 100 mL volumetric flask and adjust the volume with blank electrolyte to prepare a tannic acid solution with a concentration of 0.01 mol / L;

[0060] Dissolve 0.0162g of ferric chloride in 80mL of the blank electrolyte, then transfer the solution to a 100mL volumetric flask, use the blank electrolyte to make up to volume, and prepare a free iron ion solution with a concentration of 1mmol / L; then dilute the free iron ion solution with a concentration of 1mmol / L into: 0.1mmol / L free iron ion solution, 0.03mmol / L free iron ion solution, 0.01mmol / L free iron ion solution, 0.005mmol / L free iron ion solution and 0.001mmol / L free iron ion solution respectively through a volumetric flask;

[0061] S2: 2 mL of the tannic acid solution is mixed with 2.5 mL of free iron ion solutions of different concentrations respectively to form a complex between the tannic acid and the free iron ions, and then the mixture is transferred to a 5 mL volumetric flask and fixed to volume with the blank electrolyte to obtain at least 5 mixed solutions;

[0062] S3: using the blank electrolyte as a reference solution, measuring the absorbance of at least five mixed solutions at 512 nm using a UV-visible spectrophotometer, and fitting a standard curve using the absorbance as the ordinate and the free iron ion concentration as the abscissa;

[0063] The linear equation of the obtained standard curve is A = 0.0314 + 11.49C, and the correlation coefficient is R 2 The value was 0.9968, indicating that the standard curve had a good linear relationship within the concentration range (R 2 >0.9900);

[0064] Where A represents the absorbance at 512 nm; C represents the free iron ion concentration in the electrolyte to be measured, mmo1 / L.

[0065] Sample determination:

[0066] The electrolyte to be measured is an electrolyte obtained by injecting the blank electrolyte into a lithium-ion battery and then forming the electrolyte;

[0067] (1) 2.5 mL of the electrolyte to be measured was mixed with 2 mL of a 0.01 mol / L tannic acid solution to form a complex with the tannic acid and the free iron ions, and then the mixture was transferred to a 5 mL volumetric flask and fixed to volume with the blank electrolyte to obtain a mixed solution;

[0068] (2) Using the blank electrolyte as a reference solution, the absorbance of the mixed solution at 512 nm was measured using an ultraviolet-visible spectrophotometer, and the free iron ion concentration in the electrolyte to be measured was calculated based on the obtained absorbance and the linear equation of the standard curve.

[0069] According to the above process, 10 parallel tests were carried out, and the results are shown in Table 2.

[0070] Table 2

[0071]

[0072] As can be seen from Table 2, the discreteness of the determination method disclosed in the present invention is low and the reproducibility is high, which can meet the control of the quality of lithium-ion batteries.

[0073] Example 3

[0074] This embodiment provides a method for determining the concentration of free iron ions in a lithium ion battery electrolyte, the method comprising:

[0075] Prepare blank electrolyte:

[0076] The solvent composition is dimethyl carbonate:ethylene carbonate=1:1 (volume ratio);

[0077] The solute is 1 mol / L lithium hexafluorophosphate;

[0078] S1: Dissolve 1.7 g of tannic acid in 80 mL of blank electrolyte, then transfer the solution to a 100 mL volumetric flask and adjust the volume with blank electrolyte to prepare a tannic acid solution with a concentration of 0.01 mol / L;

[0079] Dissolve 0.0162g of ferric chloride in 80mL of the blank electrolyte, then transfer the solution to a 100mL volumetric flask, use the blank electrolyte to make up to volume, and prepare a free iron ion solution with a concentration of 1mmol / L; then dilute the free iron ion solution with a concentration of 1mmol / L into: 0.1mmol / L free iron ion solution, 0.03mmol / L free iron ion solution, 0.01mmol / L free iron ion solution, 0.005mmol / L free iron ion solution and 0.001mmol / L free iron ion solution respectively through a volumetric flask;

[0080] S2: 2 mL of the tannic acid solution is mixed with 2.5 mL of free iron ion solutions of different concentrations respectively to form a complex between the tannic acid and the free iron ions, and then the mixture is transferred to a 5 mL volumetric flask and fixed to volume with the blank electrolyte to obtain at least 5 mixed solutions;

[0081] S3: using the blank electrolyte as a reference solution, measuring the absorbance of at least five mixed solutions at 512 nm using a UV-visible spectrophotometer, and fitting a standard curve using the absorbance as the ordinate and the free iron ion concentration as the abscissa;

[0082] The linear equation of the obtained standard curve is A = 0.0374 + 13.58C, and the correlation coefficient is R 2The value was 0.99876, indicating that the standard curve had a good linear relationship within the concentration range (R 2 >0.9900);

[0083] Where A represents the absorbance at 512 nm; C represents the free iron ion concentration in the electrolyte to be measured, mmo1 / L.

[0084] Sample determination:

[0085] The electrolyte to be measured is an electrolyte obtained by injecting the blank electrolyte into a lithium-ion battery and then forming the electrolyte;

[0086] (1) 2.5 mL of the electrolyte to be measured was mixed with 2 mL of a 0.01 mol / L tannic acid solution to form a complex with the tannic acid and the free iron ions, and then the mixture was transferred to a 5 mL volumetric flask and fixed to volume with the blank electrolyte to obtain a mixed solution;

[0087] (2) Using the blank electrolyte as a reference solution, the absorbance of the mixed solution at 512 nm was measured using an ultraviolet-visible spectrophotometer, and the free iron ion concentration in the electrolyte to be measured was calculated based on the obtained absorbance and the linear equation of the standard curve.

[0088] According to the above process, 10 parallel tests were carried out, and the results are shown in Table 3.

[0089] Table 3

[0090]

[0091] As can be seen from Table 3, the discreteness of the determination method disclosed in the present invention is low and the reproducibility is high, which can meet the control of the quality of lithium-ion batteries.

[0092] Further, the iron ion concentration in the electrolyte to be measured was determined by inductively coupled plasma-mass spectrometry. The relative error between the free iron ion concentration (average value of 10 measurements) obtained by the disclosed method and the iron ion concentration determined by inductively coupled plasma-mass spectrometry was calculated, and the results were also shown in Table 4.

[0093] Table 4

[0094]

[0095]

[0096] It can be seen from Table 4 that the free iron ion concentration in the electrolyte obtained by the method disclosed in the present invention has a high accuracy, and the relative error with the measurement result of inductively coupled plasma-mass spectrometry does not exceed 6%.

[0097] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0098] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for determining the concentration of free iron ions in a lithium ion battery electrolyte, characterized in that: The method comprises: To create a standard curve: S1: Mix the iron source with the blank electrolyte to prepare at least three free iron ion standard solutions with different concentrations; S2: mixing tannic acid with free iron ion standard solutions of different concentrations respectively, so that tannic acid and free iron ions form a complex, and at least three mixed solutions are obtained accordingly; S3: using the blank electrolyte as a reference solution, measuring the absorbance of the at least three mixed solutions at 512 nm using a UV-visible spectrophotometer, and establishing a standard curve of absorbance-free iron ion concentration; Sample determination: (1) mixing the electrolyte to be measured with tannic acid, so that the tannic acid forms a complex with the free iron ions in the electrolyte to be measured, thereby obtaining a mixed solution to be measured; (2) Using the blank electrolyte as a reference solution, the absorbance of the mixed solution to be measured at 512 nm is measured using an ultraviolet-visible spectrophotometer, and the obtained absorbance data is substituted into the standard curve to calculate the free iron ion concentration in the electrolyte to be measured.

2. The method according to claim 1, characterized in that The tannic acid is added in the form of a tannic acid solution; The solvent in the tannic acid solution is a blank electrolyte, and the concentration of tannic acid is 0.001-0.01 mol / L.

3. The method according to claim 1 or 2, characterized in that: In step S2, the molar ratio of the tannic acid to the free iron ions in the standard solution is greater than 3, preferably 4-4.

5.

4. The method according to any one of claims 1 to 3, characterized in that: In step S1, the iron source includes ferric chloride.

5. The method according to any one of claims 1 to 4, characterized in that: In step S2, the concentration range of the iron element in the at least three mixed solutions is 0.0005-0.05 mmol / L.

6. The method according to claim 5, characterized in that In step S1, the concentration range of the free iron ion standard solutions with different concentrations is 0.001-0.1 mmol / L.

Citation Information

Cited By

  • Method for detecting iron dissolution amount based on chromogenic reaction and application thereof

    CN121499478A